China’s Non-interference Policy towards Western Sahara Conflict - Pedro Sobral, Wu Wanjun e (Africana Studia, 2020)
This article intends to present an overview of the Chinese stance and policies towards the still ongoing conflict in the Western Sahara region, as well as of its interaction with the players in the said conflict, Morocco and Algeria. A growing presence in the African continent, China has maintained a pragmatic neutrality towards the Western Sahara conflict, which is in line with China’s longstanding “Five Principles of Peaceful Coexistence” and non- -interference policy. China also shares common ground with Morocco on its position towards the Taiwan issue. China’s neutrality towards the Western Sahara issue does not affect its ever-closer diplomatic and economic relations with the two Northern African countries and serves to protect its vested interests in the region. In this article, we will analyze more closely why China maintains a non-interference policy in this and in other regional issues, as well how China has nevertheless become involved in the conflict, namely through international institutions and peacekeeping missions. Keywords: C hina, M orocco, A lgeria, Western Sahara.